Nuclear spin symmetry conservation studied by cavity ring-down spectroscopy of ammonia in a seeded supersonic jet from a pulsed slit nozzle. (2nd June 2020) - Wichmann, G.; Miloglyadov, E.; Seyfang, G.; Quack, M.
Abstract : We report high-resolution cw laser spectra of the symmetric stretching fundamental in ammonia 14 NH 3 measured with a cavity ring-down setup for mid-IR transitions (around 3300 c m − 1 ). In a supersonic jet expansion ( 0.0001 ≤ x ( N H 3 ) ≤ 0.04 seeded in Ar), we have obtained rotational temperatures below 7 K . For the gas expansion, a pulsed slit nozzle with 40 m m length and 70 µm width has been used. The measured relative line intensities demonstrate that the A and E nuclear spin symmetry isomers do not interconvert in the supersonic jet expansion under these conditions (nuclear spin symmetry conservation). The lateral velocity of the gas expansion has been probed by a Doppler profile measurement, showing a preference for an expansion with an angular distribution following Lambert's cosine law perpendicular to the slit direction and an approximate molecular velocity of about 470 m / s . The experimental setup is described in detail, also in view of high-resolution spectroscopy of chiral molecules as candidates to measure the parity violating energy difference between enantiomers with a barrier to interconversion around 2500 c m − 1 . GRAPHICAL ABSTRACT: